2018
DOI: 10.1111/ddi.12739
|View full text |Cite
|
Sign up to set email alerts
|

Integrating multiple data sources for assessing blue whale abundance and distribution in Chilean Northern Patagonia

Abstract: Aim Species distribution models are useful tools for depicting important habitat, assessing abundance and orienting conservation efforts. For small populations in poorly studied ecosystems, available data are often scarce and patchy. To overcome this limitation, we aim to evaluate the use of different data types within a hierarchical Bayesian framework with the goal of modelling the abundance and distribution of a small and highly migratory population of blue whale (BW, Balaenoptera musculus) summering in Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 73 publications
1
33
1
Order By: Relevance
“…Previous studies on blue whale occurrence and movement patterns indicated that until the onset of austral autumn/winter migration, blue whales focus most of their activities within these productive coastal waters 12 15 . However, variations in how this population utilizes this region and other areas within the ESP appear to result from changes in prevailing oceanographic conditions 16 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies on blue whale occurrence and movement patterns indicated that until the onset of austral autumn/winter migration, blue whales focus most of their activities within these productive coastal waters 12 15 . However, variations in how this population utilizes this region and other areas within the ESP appear to result from changes in prevailing oceanographic conditions 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Species distribution models (SDM) have shown that austral spring chlorophyll- a concentration, prior to the whales’ arrival, and thermal fronts are important oceanographic proxies for describing the abundance and distribution patterns of blue whales within the NCP 16 . Krill, the primary prey of blue whales 17 , can take advantage of seasonally enhanced productivity for biomass production, with some time lag linking early life-history stages ( e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that research on marine mammals in Patagonia should become more important for aquaculture activities in Chile because a new US trade rule requires countries to demonstrate that their fishery and aquaculture activities are equivalent in effectiveness to the US Marine Mammal Protection Act or risk losing the permit to export seafood products to the US market (Williams et al 2016;Bedriñana-Romano et al 2018).…”
Section: Interaction Of Salmon Farms With Marine Mammals Birds and Smentioning
confidence: 99%
“…There is tremendous interest in understanding if and how cetacean populations are recovering following the cessation of intense commercial whaling, yet their extensive ranges and high level of mobility combine with the challenges of research at sea to leave them poorly studied in many regions. While many cetacean species favor shelf edges and other zones of deep-water upwelling across ocean basins [14], most cetacean research is focused on coastal areas where populations may be concentrated at key times of the year and are logistically easier to survey. Far less work has been done to understand patterns of cetacean habitat use along distant continental shelf regions, and limited cetacean surveys in deep-water habitat may skew our understanding about preferred habitat [5].…”
Section: Introductionmentioning
confidence: 99%